Percolative sulfide core formation in oxidized planetary bodies - Samuel D. Crossley; Jacob B. Setera; Brendan A. Anzures; Kayla Iacovino; Wayne P. Buckley; Scott A. Eckley; Evan W. O’Neal; Jessica A. Maisano; Justin I. Simon; Kevin Righter (Nature Communications)
Abstract Models of planetary core formation traditionally involve the fractionation of Fe,Ni-metal melts from silicate mantles after extensive silicate melting. However, in planetary bodies that form farther from their central star, where moderately volatile elements are more abundant, high concentrations of oxygen and sulfur stabilize Fe,Ni-sulfides over metals. Here we show that percolative sulfide melt migration can occur in primitive, oxidized mineral assemblages prior to silicate melting in partial melting experiments with meteorites. Complementary experiments with partially molten synthetic sulfides show that fractionation of liquid sulfide from solid residues yields distinct noble metal (Os, Ru, Ir, Pd, and Pt) trace element proportions that match those manifested in the most oxidized meteoritic residues, the brachinites, as well as their complementary basaltic silicate melts. Our experiments provide robust evidence for percolative sulfide melt fractionation in meteorites and indicate that sulfide-dominated cores would be expected in oxidized planetary bodies, including Mars.